2015
DOI: 10.1002/jbm.b.33381
|View full text |Cite
|
Sign up to set email alerts
|

Influence of collagen source on fibrillar architecture and properties of vitrified collagen membranes

Abstract: Collagen vitrigel membranes are transparent biomaterials characterized by a densely organized, fibrillar nanostructure that show promise in the treatment of corneal injury and disease. In this study, the influence of different type I collagen sources and processing techniques, including acid-solubilized collagen from bovine dermis (Bov), pepsin-solubilized collagen from human fibroblast cell culture (HuCC), and ficin-solubilized collagen from recombinant human collagen expressed in tobacco leaves (rH), on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The influence of the collagen source on the physical and structural properties of resulting materials is known 59 and was therefore addressed by characterising both native as well as functionalised and crosslinked states.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the collagen source on the physical and structural properties of resulting materials is known 59 and was therefore addressed by characterising both native as well as functionalised and crosslinked states.…”
Section: Discussionmentioning
confidence: 99%
“…9Eii-iii) [228]. Vitrigel membranes are another group of prefabricated patches (described in section 3.1.3) [163,232]. Chae et al developed a collagen vitrigel membrane that could help reconstruction of the corneal epithelial layer and prevent epithelial hypertrophy, minimizing complications such as immune rejection or delay in epithelialization [163].…”
Section: Bandage Contact Lenses and Prefabricated Patchesmentioning
confidence: 99%
“…In contrast, both human COLIs demonstrated higher light transmission compared to the bovine COLI. When comparing the structure of the vitrigels formed from each COLI, both the bovine and cell culture derived COLI had randomly oriented, disorganized fibrillar structures, whereas those formed from the recombinant human COLI displayed remarkable fibril alignment, which was unaffected by crosslinking . These results confirm that COLI source can have an effect on the properties and performance, although it would also be useful to see a comparison of the bovine COLI to the more commonly used medical grade porcine and rat tail collagens.…”
Section: Naturally Derived Biomaterials Used For Corneal Tissue Enginmentioning
confidence: 71%
“…To determine the effect of these variables, vitrigel membranes were fabricated from three different sources of COLI: i) acid‐solubilized from bovine dermis, ii) pepsin‐solubilized from human fibroblast cell culture, and iii) ficin‐solubilized recombinant human COLI from tobacco leaves . The pH required for vitrification, fibrillar organization, light transmission, denaturation temperature, tensile strength, thickness, and hydration‐state of regular and crosslinked vitrigels were then compared . It was found that regardless of COLI source, a pH of 3 was necessary for the formation of a clear vitrigel and higher concentrations of both human COLIs were necessary to form vitrigels with similar handling characteristics to the bovine vitrigels .…”
Section: Naturally Derived Biomaterials Used For Corneal Tissue Enginmentioning
confidence: 99%